Thrombectomy versus medical management for isolated anterior cerebral artery stroke: an international multicenter registry study - Meyer, Lukas; Stracke, Paul; Broocks, Gabriel; Elsharkawy, Mohamed; Sporns, Peter B.; Piechowiak, Eike Immo; Kaesmacher, Johannes; Maegerlein, Christian; Hernández Petzsche, Moritz Roman; Zimmermann, Hanna; Naziri, Weis; Abdullayev, Nuran; et al. (Radiology, 2023)
Background - - Evidence supporting a potential benefit of thrombectomy for distal medium vessel occlusions (DMVOs) of the anterior cerebral artery (ACA) is, to the knowledge of the authors, unknown. - - Purpose - - To compare the clinical and safety outcomes between mechanical thrombectomy (MT) and best medical treatment (BMT) with or without intravenous thrombolysis for primary isolated ACA DMVOs. - - Materials and Methods - - Treatment for Primary Medium Vessel Occlusion Stroke, or TOPMOST, is an international, retrospective, multicenter, observational registry of patients treated for DMVO in daily practice. Patients treated with thrombectomy or BMT alone for primary ACA DMVO distal to the A1 segment between January 2013 and October 2021 were analyzed and compared by one-to-one propensity score matching (PSM). Early outcome was measured by the median improvement of National Institutes of Health Stroke Scale (NIHSS) scores at 24 hours. Favorable functional outcome was defined as modified Rankin scale scores of 0-2 at 90 days. Safety was assessed by the occurrence of symptomatic intracerebral hemorrhage and mortality. - - Results - - Of 154 patients (median age, 77 years; quartile 1 [Q1] to quartile 3 [Q3], 66-84 years; 80 men; 94 patients with MT; 60 patients with BMT) who met the inclusion criteria, 110 patients (median age, 76 years; Q1-Q3, 67-83 years; 50 men; 55 patients with MT; 55 patients with BMT) were matched. DMVOs were in A2 (82 patients; 53%), A3 (69 patients; 45%), and A3 (three patients; 2%). After PSM, the median 24-hour NIHSS point decrease was −2 (Q1-Q3, −4 to 0) in the thrombectomy and −1 (Q1-Q3, −4 to 1.25) in the BMT cohort (P = .52). Favorable functional outcome (MT vs BMT, 18 of 37 [49%] vs 19 of 39 [49%], respectively; P = .99) and mortality (MT vs BMT, eight of 37 [22%] vs 12 of 39 [31%], respectively; P = .36) were similar in both groups. Symptomatic intracranial hemorrhage occurred in three (2%) of 154 patients. - - Conclusion - - Thrombectomy appears to be a safe and technically feasible treatment option for primary isolated anterior cerebral artery occlusions in the A2 and A3 segment with clinical outcomes similar to best medical treatment with and without intravenous thrombolysis.